EG-CB-BM Framework: Strategic Insights into the Impact of Electronic Gadgets on Consumer Behavior in the Digital Business Management Landscape - Srivastav , Tushar; Singh, Mridulesh (Journal of Neonatal Surgery, 2025)
This paper introduces the EG-CB-BM (Electronic Gadgets–Consumer Behavior–Business Management) Framework, developed to examine the strategic impact of digital devices on consumer choices within a rapidly transforming digital economy. Drawing on current literature, the study explores the digital evolution of consumer behavior and how electronic gadgets facilitate interaction within omnichannel environments. It synthesizes the status of digital marketing and its role in reshaping business processes and marketing strategies. Through case analyses of Facebook, Instagram, YouTube, Amazon, Twitter, Snapchat, the paper highlights the critical influence of platform-specific dynamics on customer engagement. Key prospects and limitations are discussed, with an emphasis on the need for adaptive digital business models. This research contributes practical insights into how enterprises can align technology, consumer behavior, and marketing strategies to achieve sustainable competitive advantage.